Keratosis pilaris rubra faciei/Atopic dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Keratosis pilaris is a genetically determined disorder transmitted by an autosomal dominant trait. It is characterized by hyperkeratosis of the follicular openings, namely the external orifices of the pilo-sebaceous ducts. When keratosis pilaris is associated with intense perifollicular erythema we talk about keratosis pilaris rubra. The latter condition should be differentiated from atopic dermatitis.